Pembuatan Bioplastik Ramah Lingkungan Dari Kitosan Dengan Bahan Baku Limbah Sisik Ikan Nila Dan Ikan Kakap - elvina, Wica; Utami, Risnita Tri (Jurnal Akuakultur Sungai dan Danau, 2025)
Chitosan is the result of modifying the chitin compound by removing the acetyl group and leaving the amine group. Chitin compounds can be obtained from proteins contained in the outer skin/scales of fish and shrimp commodities. Discarded fish scales can be used to make chitosan as a basic material for making bioplastics. This research was carried out with the aim of optimizing the benefits of unused fish scales into products that have economic value and can be reused by the community, one of which is bioplastic. The fish scales used are fish scales that have the greatest potential in Bengkulu province, namely snapper fish scales and tilapia fish scales. Making bioplastics is done by extracting fish scales into chitin compounds then going through a deacetylation process to become chitosan, then the chitosan is given the additional ingredient glycerol to form bioplastics. The results of the research by adding 0.5 ml and 1 ml of glycerol to the chitosan from each fish scale, showed that the resulting bioplastic was in the form of a solid with a transparent sheet shape with a slight yellow-gray shade. In general, there is no difference in tilapia fish scales and snapper scales. The difference is only visible in the texture of the bioplastic with the 0.5 ml glycerol mixture looking stiffer, while the 1 ml glycerol mixture looks more flexible. It is hoped that bioplastics made from natural ingredients, such as fish scales, can become a more biodegradable product and can help reduce fisheries waste.